2023
DOI: 10.3390/pr11030914
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring PM2.5 at a Large Shopping Mall: A Case Study in Macao

Abstract: Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. The concentration of particulate matters (PM) produced by the interior renovation of shopping malls has not received particular attention in Macao. Therefore, this study will investigate the indoor air quality (IAQ), in particular of PM2.5, in large-scale shopping mall renovation projects. This study collected on-site PM data with low-cost portable monitoring equipment placed temporarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similarly, in a study conducted by Challoner and Gill 82 in different workplaces, higher indoor environmental levels were measured during working hours compared to other hours. Also, in the other study conducted by Lei et al, 83 indoor PM 2.5 levels were measured in the public area of a shopping mall and the average daily value was found to be 20.14 µg/m 3 . In this study, indoor PM 2.5 concentrations measured at all retail stores during busy hours of both seasons were found to be higher than the levels measured in the study carried out by Lei et al 83 In general, the results obtained in this study indicated that PM 2.5 concentrations varied due to several factors, such as the presence of strong indoor sources, activities, ventilation effect, building's location and traffic density around the building.…”
Section: Pm 25 Mass Concentrations In Winter and Summer Seasonsmentioning
confidence: 74%
“…Similarly, in a study conducted by Challoner and Gill 82 in different workplaces, higher indoor environmental levels were measured during working hours compared to other hours. Also, in the other study conducted by Lei et al, 83 indoor PM 2.5 levels were measured in the public area of a shopping mall and the average daily value was found to be 20.14 µg/m 3 . In this study, indoor PM 2.5 concentrations measured at all retail stores during busy hours of both seasons were found to be higher than the levels measured in the study carried out by Lei et al 83 In general, the results obtained in this study indicated that PM 2.5 concentrations varied due to several factors, such as the presence of strong indoor sources, activities, ventilation effect, building's location and traffic density around the building.…”
Section: Pm 25 Mass Concentrations In Winter and Summer Seasonsmentioning
confidence: 74%
“…Among the studies presented in this issue, there is one that reports a crowdsensing-based vehicle sensor network system for real-time monitoring of urban PM levels, discussing its costeffectiveness and benefits [7]. The impact of poor indoor air quality on work efficiency is examined through a case study of PM2.5 levels in a large shopping mall in Macao [8].…”
mentioning
confidence: 99%